The Role Of Oic Countries In The Development Of The Dinar Dirham As An Alternative To World Currency - Erwin Febriansyah; Arina Azwani; Teddy Rianto L Gaol (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Islamic Organization Cooperation has been doing it for a long time agreement Work The same economy trade . OIC has 57 member countries, one of which is Indonesia system mark swap floating free . Exchange rate is something matter important thing to do noticed by everyone government Because every movement appreciation and depreciation mark swap influence economy a country. Phenomenon weakening mark commodity the current dollar currency This become the strongest currency in the world becomes opportunity for Islamic countries to developing Dinars and Dirhams because own mark physical and value intrinsic ones are not changed from formerly . Stability level a country 's currency only can materialized If commodities and values eye the money No changed or not can affected by turmoil economy or geopolitics in the world. With use Vector Error Correction Model (VECM) approach for test possibility the role of OIC countries in application of Dinar Dirham as world alternative currencies . The result show response inflation to mark swap seen that mark always exchange​ is on the equilibrium line from period 1 to 10 though happen inflation in the period secondly , meaning Dinar and Dirham currencies are not can influenced by inflation.